(untitled) (Rudarsko-geološko-naftni zbornik, 2020)
The results of monitoring light pollution near the center of Zagreb at the Faculty of Mining, Geology and Petroleum Engineering (RGN) for the period 2012 - 2017 were presented in a recent article (Andreić, 2018). The question that re- mained unanswered is how the night sky brightness behaves in the suburbs of Zagreb and in the nearby rural area. This article attempts to give some answers to this question by analyzing data gathered at the rural site of Merenje, located north of Zagreb. The main conclusion drawn is that the night sky brightness at both sites follows very similar patterns for clear sky conditions and is often similar for cloudy conditions, too. For both sites, no significant increase in zenithal night sky brightness was found in the observed period of 2014 - 2017. Thus, at least for the areas north of Zagreb that are in the shadow of Medvednica Mountain, the contribution of the light pollution from Zagreb and its growing outskirts remains unaltered. The main difference is in the level of the night sky brightness, the average for the RGN site being 16.9 mag/ arcsec2 and 18.9 mag/arcsec2 for the Merenje site. Additionally, the cloudy conditions enhance the light pollution of Za- greb a lot more, the difference being about 3.2 mag/arcsec2 for RGN, in contrast to 1.9 mag/arcsec2 for the Merenje site. No measurements exist for areas to the south, so no conclusions can be made for the situation there. Last, but not least, it was found that in cloudy conditions, the stronger light pollution of Zagreb is proportionally more enhanced by the clouds/fog than the smaller levels of light pollution at the Merenje site.